1337 IMPROVING THE PERI-OPERATIVE MANAGEMENT OF ANTICOAGULATION IN PATIENTS WITH NECK OF FEMUR FRACTURES (NOFFS). (16th January 2023) - Knight, M; Sommar, D; Mufti, S
Abstract: Introduction: Neck of femur fractures (NOFFs) are a clinically significant diagnosis, with 10% of patients dying within one month of diagnosis [1]. There is a strong association between earlier surgery and improvement in postoperative outcomes [2]. Taking anticoagulation can cause delays in patients being operated on. At Homerton University Hospital (HUH), no previous guideline existed to aid specifically in the management of patients with NOFFs on anticoagulation. We created a guideline in order to reduce delays to theatre, in keeping with national guidance (<36 hours to operation). Methods: We audited all patients in 2020 admitted to HUH with NOFFs taking anticoagulation. A guideline was then created, reflecting new national guidance [3] on the management of anticoagulation pre-operatively for NOFF patients. Three PDSA cycles were completed, with repeat audit cycles following dissemination and teaching of guideline to relevant clinical groups. Results: Following implementation of our guideline, 56% of patients had surgery within 36 hours of admission, compared to 25% previously. Advice being given to the admitting team regarding timing of the operation was more consistent, and the admitting team needed to ask for advice less often. There was an overall increase in consistency of management. Conclusions: Ensuring NOFFs are operated on promptly reduces the risk of co-morbidity and mortality [2]. There are often incorrect delays to theatre following anticoagulation administration due to perceived risk of bleeding. We created and implemented a new guideline, which successfully reduced time taken for patients on anticoagulation to be taken to theatre for operation. References: [1] NICE. 'Hip Fracture: Management'. Clinical guideline. Published: 22 June 2011. Accessed at: nice.org.uk/guidance/cg124 . [2] Seong YJ, Shin WC, Moon NH, Suh KT. Timing of Hip-fracture Surgery in Elderly Patients. Hip Pelvis. 2020;32(1):11-16. doi: 10.5371/hp.2020.32.1.11 . [3] Griffiths R, Babu S, Dixon P et al. Ray), Guideline for the management of hip fractures. Anaesthesia 2020; 76: 225–37.